Efektivitas Media Whatsapp Blast Dalam Meningkatkan Kesadaran Pemeliharaan Kesehatan Gigi Dan Mulut Pada Remaja - Malika, Ajeng Sri Intan; Laut, Deru Marah; Mulyanti, Sri; Chaerudin, Denden Ridwan (Jurnal Terapi Gigi dan Mulut, 2024)
An alternative strategy to prevent several diseases that may appear in the oral cavity is to maintain healthy teeth and mouth. Unfortunately, there is still a lack of knowledge among Indonesian teenagers regarding the importance of maintaining healthy teeth and mouth. Therefore, education is needed to increase awareness of these issues, and one way is through educational media such as WhatsApp Blast. The aim of this research is to find out how well the WhatsApp Blast media works in increasing teenagers' awareness of dental and oral health problems. Thirty-five adolescents in one group participated in a pre-experimental pretest-posttest design research method. Purposive sampling is a sampling method. Adolescents' awareness of maintaining dental health and WhatsApp Blast Media are research variables. Experts in the field of media and materials have tested WhatsApp Blast media. There is a significant difference in awareness between levels before and after intervention, as shown by the results of the Wilcoxon test, which has a p value of 0.000 < 0.05. After the intervention, 82.9% of adolescents had a high level of awareness, compared to 91.4% of adolescents who had a moderate level of awareness before. Research findings show that WhatsApp Blast helps teenagers become more aware of their oral and dental health.